PENGEMBANGAN KARTU BUDAYA INDONESIA (KABUSA) PADA KELAS IV SEKOLAH DASAR - Cahyati, Intan; Dian Lestari, Neta; Lara Syaflin, Sylvia (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The problem with this research is that students have difficulty understanding the material on the forms of cultural diversity in Indonesia, especially on the island of Sumatra, as well as the lack of use of learning media. This research aims to produce learning media for Indonesian cultural cards (kabusa) that are valid, practical and effective. The method used is the ADDIE model (Analysis, Design, Development, Implementation and Evaluation). The research results showed that the Indonesian cultural card learning media (kabusa) that was developed met the "Very Valid" criteria because it obtained a validity value of 81.61%. Based on the one to one evaluation trial, it obtained a practicality score of 90% for the "Very Practical" criteria and based on the small group evaluation trial it obtained a score of 87.81% for the "Very Practical" criterion. Based on field test trials from student test questions, an N-Gain value of 0.7755 was obtained for the "High" criteria and an N-Gain percent value of 77.512%, which means the use of Indonesian cultural card media (kabusa) with the criteria "Effective" for use.